2019
DOI: 10.1109/tcyb.2018.2804340
|View full text |Cite
|
Sign up to set email alerts
|

Double-Loop Stability for High Frequency Networked Control Systems Subject to Actuator Saturation

Abstract: This paper generalizes stability for a high frequency networked control system (NCS) subject to actuator saturation via integral quadratic constraints. A delta operator system with a high frequency constraint is used to model the high frequency NCS. Double-loop stability is treated via outer-loop and interloop feedback configurations for the high frequency NCS. Stability criteria are derived with the high frequency constraint and actuator saturation by a generalized Kalman-Yakubovich-Popov lemma. Numerical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…PI control is the most commonly used control method for photovoltaic grid-connected inverter to track the power-grid current, but its ability to suppress low-order harmonics is weak. The above derivation and verification process can be concluded that the whole controller u t_c is composed of PI controller u c and a feedforward compensator u s , which is used to compensate the nonlinear power-grid voltage perturbation, as shown in (13). In this paper, an additional compensation mechanism is added to improve the performance of the grid-connected current.…”
Section: B Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…PI control is the most commonly used control method for photovoltaic grid-connected inverter to track the power-grid current, but its ability to suppress low-order harmonics is weak. The above derivation and verification process can be concluded that the whole controller u t_c is composed of PI controller u c and a feedforward compensator u s , which is used to compensate the nonlinear power-grid voltage perturbation, as shown in (13). In this paper, an additional compensation mechanism is added to improve the performance of the grid-connected current.…”
Section: B Controller Designmentioning
confidence: 99%
“…The combined control method can reduce the steady-state error of the system and has good robustness. The logic block diagram of the controller can be obtained from (12), (13), (14), (19) and (29). Fig.4 is a Block diagram of current impulsive perturbation control model for grid-connected inverters.…”
Section: B Controller Designmentioning
confidence: 99%
“…Several results have emerged by solving problems of global stabilization, semi-stabilization, and regional stability stabilization (see, among others, Chen and Wang, 2021;Du et al, 2018;Hu and Lin, 2001;Qiang and Zhang, 2018). Yang et al (2019) designed a double-loop feedback control for the high-frequency networked control system with actuator saturation. Yu et al (2010) proposed a feedback control method for the switched system with the actuator saturation .…”
Section: Introductionmentioning
confidence: 99%
“…Existing researches studied how the operating frequency effects on robust control and signal stability of NCSs [20,21]. However, at the best of our knowledge, there is no direct research about how operating frequency effects on the NCS's reliability.…”
Section: Introductionmentioning
confidence: 99%